Introduction to Devices Orchestration in Internet of Things Using SBPMN - González García, Alejandro; Álvarez Álvarez, Manuel; Pascual Espada, Jordán; Sanjuán Martínez, Óscar; Cueva Lovelle, Juan Manuel; Pelayo García-Bustelo, B. Cristina (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
In this research we try to provide an architecture that allows the orchestration of objects that are part of the Internet of things creating business processes. Internet of Things is still in full development; this implies that there is a lack of standards for its proper implementation. Among these gaps is for example the technology used to allow objects to connect to the network, since there are several options but none seems to end imposed that is why this work try to provide architecture that imposes an alternative solution to this problem. However, it is difficult to provide a common solution to all the objects used in everyday life because of its great diversity, it requires us to classify them and thus create an appropriate architecture for each of the types These architectures are designed to facilitate the devices orchestration in a similar way as is currently done with web services enabling business process modeling.
Keywords: internet of things; orchestration; BPEL; SBPMN; SOAP; WSDL; REST; WADL; IJIMAI